2011
DOI: 10.1007/s00216-011-5120-2
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanomaterials as a new tool for bioanalytical applications of laser desorption ionization mass spectrometry

Abstract: Nanomaterials have emerging importance in laser desorption ionization mass spectrometry (LDI-MS) with the ultimate objective being to overcome some of the most important limitations intrinsically related to the use of conventional organic matrices in matrix-assisted (MA) LDI-MS. This review provides a critical overview of the most recent literature on the use of gold nanomaterials as non-conventional desorption ionization promoters in LDI-MS, with particular emphasis on bioanalytical applications. Old seminal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
88
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(88 citation statements)
references
References 95 publications
0
88
0
Order By: Relevance
“…Silver salt was used in laser desorption/ionization (LDI) by depositing a small layer of AgNO 3 for the analysis of hydrocarbons in oil [14,15]. In the past few years, several reviews demonstrated growing interest in silver nanoparticles (AgNP) [16] and gold nanoparticles (AuNP) [17] to facilitate LDI. AgNP were previously used in surface-assisted laser desorption imaging (SALDI) [18,19] for drug analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Silver salt was used in laser desorption/ionization (LDI) by depositing a small layer of AgNO 3 for the analysis of hydrocarbons in oil [14,15]. In the past few years, several reviews demonstrated growing interest in silver nanoparticles (AgNP) [16] and gold nanoparticles (AuNP) [17] to facilitate LDI. AgNP were previously used in surface-assisted laser desorption imaging (SALDI) [18,19] for drug analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Gold clusters provide simple and fast determination of accurate mass compared with common calibration standards, such as peptides or proteins. Moreover, AuNPs can enhance ionization in various techniques, such as surface-assisted laser desorption ionization (SALDI), nanoparticle-assisted laser desorption ionization (NALDI), and gold nanoparticle-assisted laser desorption ionization (GALDI) [20][21][22]. The structure and properties of gold and phosphorus clusters are well known [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Applications to several structural types 97 (Pilolli et al, 2012) Short general review on characterization of mainly acidic glycans GAGs N-links, glycan arrays 224 ) Application of surface plasmon resonance for the detection of carbohydrates and glycoconjugates Section on MALDI and in combination with SPR 201 (Safina, 2012) TLC/HPTLC with mass spectrometric detection A review of the progress in the last 5 years 98 Thin-layer chromatography and mass spectrometry for the separation and detection of large and small biomolecules Several compound typescarbohydrates peptides etc. 228 (Tuzimski, 2011) -on-aReview of reactions performed on MALDI plates.…”
Section: Theorymentioning
confidence: 99%